2009
DOI: 10.1074/jbc.m109.043752
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Studies of Claudin Extracellular Domains by Cysteine-scanning Mutagenesis

Abstract: Claudins form size-and charge-selective pores in the tight junction that control the paracellular flux of inorganic ions and small molecules. However, the structural basis for ion selectivity of paracellular pores is poorly understood. Here we applied cysteine scanning to map the paracellular pathway of ion permeation across claudin-2-transfected Madin-Darby canine kidney type I cells. Four potential pore-lining amino acid residues in the first extracellular loop were mutated to cysteine and screened for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
94
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 35 publications
7
94
0
Order By: Relevance
“…Thus, the results from the screening phase for G37C and S58C were false positives. We previously showed that MTS inhibition of claudin-2 I66C was due to partial steric block of the paracellular cation pore (14). We therefore reasoned that differences in the magnitude of inhibition of conductance of our cysteine mutants by thiol-reactive reagents of different size or charge ought to be informative about the geometrical location of each mutated residue within the pore.…”
Section: Characterization Of Monoclonal Mdck I Tet-off Cell Lines Expmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the results from the screening phase for G37C and S58C were false positives. We previously showed that MTS inhibition of claudin-2 I66C was due to partial steric block of the paracellular cation pore (14). We therefore reasoned that differences in the magnitude of inhibition of conductance of our cysteine mutants by thiol-reactive reagents of different size or charge ought to be informative about the geometrical location of each mutated residue within the pore.…”
Section: Characterization Of Monoclonal Mdck I Tet-off Cell Lines Expmentioning
confidence: 99%
“…In addition, we included I66C, a known pore-lining residue mutant (14), as a positive control. Inducible protein expression was verified by immunoblotting (Fig.…”
Section: Characterization Of Monoclonal Mdck I Tet-off Cell Lines Expmentioning
confidence: 99%
See 2 more Smart Citations
“…First evidence for channel formation came from structural and functional studies demonstrating that modification of the first extracellular loop of claudins affects the conductive properties of claudintransfected cells 85,86 . For example, the cation-selective claudin-2 contains a critical residue in its first extracellular loop that, if replaced with a cysteine followed by modification with the thiolreactive bulky reagent methanethiosulfonate was found to block the ion-conductive pathway 87,88 . …”
mentioning
confidence: 99%